Excellence and the Promotion of Creativity and Innovation in Education (Journal of Universal Excellence, 2026)
Research question (RV): Is excellence and promotion of creativity and innovation in education demonstrated.Purpose: To identify and analyze the assessment of the fundamental building block of the EFQM model of excellence - creativity and innovation. Make suggestions for improvement based on the findings.Method: Using a qualitative method, reviewing professional and scientific literature, using a research method with analytical analysis and extracting the essence and findings from them.Results: The results showed that it is necessary to systematically enable a greater flow of exchange of good experiences among professionals. Criteria are the basis for answering how we will know we have achieved a goal. The results according to FOŠmetr showed that organizations have a well-developed innovative and creative activity. The assessment of the building block of one's own company is also satisfactory. All the studied professional literature lists the main activities needed to continuously improve creativity in organizations.Organization: The research has a great impact on organizations, as the assessment of the building blocks of EFQM excellence in the field of creativity and innovation provided a starting point for change.Society: With the research we want to point out that this is an area in which much needs to be built in the future. In order for education to be more successful, it is necessary to encourage creativity and innovation among employees and to identify creative potentials.Originality: The contribution of the profession is in the originality of the research.Limitations / further research: Excellence and the promotion of creativity and innovation in education is a broad concept that can be explored even more widely. The research is transparent, and it would be good to do quantitative research.
Keywords: educator; creativity; encouraging creativity; innovation; role of educator; social environment